2008
DOI: 10.1021/jf703723s
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Methods To Assess Lipophilic and Hydrophilic Antioxidant Capacity of Food Extracts in Vitro

Abstract: Assays comprising three probes for different mechanisms of antioxidant activity in food products have been modified to allow better comparison of the contributions of the different mechanisms to antioxidant capacity (AOC). Incorporation of a common format for oxygen radical absorbance capacity (ORAC), ferric reducing antioxidant power (FRAP), and iron(II) chelating activity (ICA) assays using 96-well microplates provides a comprehensive and high-throughput assessment of the antioxidant capacity of food extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 41 publications
(75 reference statements)
4
43
1
6
Order By: Relevance
“…Where FRAP measures the reducing capacity of all the antioxidants in the mixture, FCR records only those classed as polyphenolic compounds (Huang et al, 2005). As a result previous researchers have often found very good linear correlations between FCR and one or more SET based assays such as FRAP or ABTS •+ (Jimenez-Alvarez et al, 2008;Molan, De & Meagher, 2009;Sreeramulu & Raghunath, 2010;Stratil, Klejdus & Kuban, 2006). The same relationship is observed in the current study, where a very strong positive linear correlation (r 2 = 0.96) is observed between FRAP and FCR.…”
Section: Discussionsupporting
confidence: 86%
“…Where FRAP measures the reducing capacity of all the antioxidants in the mixture, FCR records only those classed as polyphenolic compounds (Huang et al, 2005). As a result previous researchers have often found very good linear correlations between FCR and one or more SET based assays such as FRAP or ABTS •+ (Jimenez-Alvarez et al, 2008;Molan, De & Meagher, 2009;Sreeramulu & Raghunath, 2010;Stratil, Klejdus & Kuban, 2006). The same relationship is observed in the current study, where a very strong positive linear correlation (r 2 = 0.96) is observed between FRAP and FCR.…”
Section: Discussionsupporting
confidence: 86%
“…A localização dos antioxidantes em interfaces causa um fenômeno conhecido como paradoxo polar, no qual os antioxidantes polares são mais efetivos em meios apolares e vice-versa 13 . Consistentemente com essas complexas interações moleculares, Espín et al 14 6 tenham sugerido que apenas os ensaios de TEAC e ORAC são passíveis de adaptação para os compostos lipofílicos, houve adaptações de protocolos para outros ensaios 14,19 . No Quadro 1, destacam-se algumas das principais características e diferenças entre os ensaios mais utilizados para a determinação da capacidade antioxidante de óleos vegetais.…”
Section: Métodos De Análise Da Capacidade Antioxidante Total De óLeosunclassified
“…Recentemente, os resultados desse ensaio têm sido apresentados como equivalentes de trolox 10 . Devido aos potenciais redox comparáveis do Fe +3 -TPTZ (0,70 V) e do ABTS + (0,68 V), os compostos antioxidantes que reagem no ensaio do FRAP tendem a reagir de forma similar no ensaio da TEAC, gerando resultados que se correlacionam positivamente 19 .…”
Section: Espin Et Alunclassified
See 1 more Smart Citation
“…11 In an earlier study of L-ORAC assays, 12 we revealed that the repeatability and intermediate precision of the original L-ORAC method 13 are inadequate, and thus we developed a modified method that provides satisfactory repeatability and intermediate precision in a single-laboratory validation study. Here, we conducted interlaboratory tests in accordance with an internationally harmonized protocol for the design of method-performance studies 14 to validate this improved L-ORAC method.…”
Section: Introductionmentioning
confidence: 99%